PHONO –SYNTAXICO-SEMANTIC INFLUENCES OF YIRA ON THE LEARNING OF ENGLISH - Kambale, Jean (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
This paper, entitled “Phono –syntaxico-semantic influences of Yira on the learning of English”, aims to help language teachers in general, and, more particularly, teachers of English in yira areas, become aware of the difficulties faced by Yira speakers of English. There are many elements of Yira that have a negative impact on English spoken by Yira people.